Chemo-brain: An activation likelihood estimation meta-analysis of functional magnetic resonance imaging studies. (November 2021) - Bernstein, Lori J.; Edelstein, Kim; Sharma, Alisha; Alain, Claude
Highlights: fMRI meta-analysis differentiates cancer patients treated with chemotherapy from controls. Activation likelihood estimation identifies common patterns of activity across studies. People treated with chemotherapy show hypo frontal-parietal activity across cognitive tasks. Hypo-activations reflect dysfunction in mobilizing attention resources. Chemo-brain is linked to deficits in the frontal attention network. Abstract: Adults with non-central nervous system (CNS) cancers frequently report problems in attention, memory and executive function during or after chemotherapy, referred to as cancer-related cognitive dysfunction (CRCD). Despite numerous studies investigating CRCD, there is no consensus regarding the brain areas implicated. We sought to determine if there are brain areas that consistently show either hyper- or hypo-activation in people treated with chemotherapy for non-CNS cancer (Chemo+). Using activation likelihood estimation on brain coordinates from 14 fMRI studies yielding 25 contrasts from 375 Chemo+ and 429 chemotherapy-naive controls while they performed cognitive tasks, the meta-analysis yielded two significant clusters which are part of the frontoparietal attention network, both showing lower activation in Chemo+. One cluster peaked in the left superior parietal cortex, extending into precuneus, inferior parietal lobule, and angular gyrus. The other peaked in the right superior prefrontal areas, extending into inferior prefrontal cortex. We propose that these observed lower activations reflect a dysfunction in mobilizing and/or sustaining attention due to depletion of cognitive resources. This could explain higher level of mental fatigue reported by Chemo+ and why cancer survivors report problems in a wide variety of cognitive domains.